2010
DOI: 10.2298/jas1001045p
|View full text |Cite
|
Sign up to set email alerts
|

Possibilities for utilization of tobacco stems for production of energetic briquettes

Abstract: Tobacco (Nicotiana tabacum L.) belongs to the group of plants that produce agricultural raw material. Besides leaves, which are used to satisfy the passion for smoking, tobacco can be used for producing oil and biodiesel, because it contains 30-40% of vegetable oil. Because of its content of citric acid, tobacco can be used for production of dyes and varnishes. Seed cake contains high percentage of proteins (35-44%) and can be used as livestock feed. Because of the high contents of lignin (40-45%) and ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
17
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 2 publications
2
17
0
3
Order By: Relevance
“…The HVs of the eight date palm residues were found to be in the range of some well-known biomass fuels reported in the literature, i.e., common reed (18.9 MJ/kg) [4], Calotropis procera (19.5 MJ/kg) [64], vine prunings (18.7 to 19.2 MJ/kg) [6], corncobs (17 MJ/kg) [1], and tobacco stems (17.8 MJ/kg) [2]. The heating values of bio-char produced from FEB ranged from 23 to 26 MJ¨kg´1 [65].…”
Section: Fuel Characteristics Of the Date Palm Residuesmentioning
confidence: 99%
See 2 more Smart Citations
“…The HVs of the eight date palm residues were found to be in the range of some well-known biomass fuels reported in the literature, i.e., common reed (18.9 MJ/kg) [4], Calotropis procera (19.5 MJ/kg) [64], vine prunings (18.7 to 19.2 MJ/kg) [6], corncobs (17 MJ/kg) [1], and tobacco stems (17.8 MJ/kg) [2]. The heating values of bio-char produced from FEB ranged from 23 to 26 MJ¨kg´1 [65].…”
Section: Fuel Characteristics Of the Date Palm Residuesmentioning
confidence: 99%
“…1 As a percentage of the oven-dried weight. 2 As a percentage of the free-extractives oven-dried weight. 3 Fengel and Wegener [31].…”
Section: Chemical Composition Of the Date Palm Residuesmentioning
confidence: 99%
See 1 more Smart Citation
“…Preliminary phytochemical screening of aqueous, ethanolic and methanolic extract of the stem of Nicotiana tabacum was done in order to reveal the presence of the flavonoid so that the antioxidant activity of aqueous and methanolic extract can be observed. In the previous studies, it was observed that the stem of Nicotiana tabacum consist of 0.005% nicotine 19 which signifies that any other secondary metabolites such as flavonoid would be in large amount. For this flavonoid was quantified by the aluminium colometric method in to calculate the number of flavones.…”
Section: Fig2: Rapid Screening Of Antioxidant Compound In Aqueous Exmentioning
confidence: 98%
“…As far as the stem of tobacco is concerned, production of briquettes has values of tobacco stem which consist of only minimum quantity of Nicotine i.e. 0.005% 19 . It has been reported that extracts of seeds have shown antibacterial activity against Staphylococcus.…”
mentioning
confidence: 99%